y - y₁ = m(x - x₁)
y - (-7) = -1¹/₅(x - (-3))
y + 7 = -1¹/₅(x + 3)
y + 7 = -1¹/₅(x) - 1¹/₅(3)
y + 7 = -1¹/₅x - 3³/₅

y - y₁ = m(x - x₁)
y - (-2) = -1¹/₄(x - (-9))
y + 2 = -1¹/₄(x + 9)
y + 2 = -1¹/₄(x) - 1¹/₄(9)
y + 2 = -1¹/₄x - 11¹/₄
- 2 - 2
y = -1¹/₄x - 13¹/₄
y - y₁ = m(x - x₁)
y - (-3) = ⁻¹/₄(x - 8)
y + 3 = ⁻¹/₄(x) + ¹/₄(8)
y + 3 = ⁻¹/₄x + 2
- 3 - 3
y = ⁻¹/₄x - 1
y - y₁ = m(x - x₁)
y - (-17) = ¹/₂(x - (-6))
y + 17 = ¹/₂(x + 6)
y + 17 = ¹/₂(x) + ¹/₂(6)
y + 17 = ¹/₂x + 3
- 17 - 17
y = ¹/₂x - 14

y - y₁ = m(x - x₁)
y - 8 = 1¹/₅(x - 6)
y - 8 = 1¹/₅(x) - 1¹/₅(6)
y - 8 = 1¹/₅x - 7¹/₅
+ 8 + 8
y = 1¹/₅x + ⁴/₅